Supreme Court's Decision Regarding the Prohibition of Interfaith Marriage and Its Relevance of Maqaṣid Al-Shari'ah - Aziz, Abdul; Hakim, Lukman; Subhan Nugraha, Iqbal; Aminudin, Sugeng (Jurnal Hukum Islam, 2024)
Interfaith marriage is still a debate, especially after the issuance of the Circular of the Supreme Court of the Republic of Indonesia concerning the prohibition of registration of interfaith marriages, which is considered to injure Human Rights. This research discusses the relevance of the Supreme Court's Decision on interfaith marriage with the principles of maqāṣid al-sharī'ah and its implications for the right to freedom of choice of partner. This normative legal research uses a legislative, conceptual, philosophical and case approach. The sources of legal materials are the Circular of the Supreme Court and several Supreme Court decisions related to interfaith marriages in the last three years. The results show that the ratio legis of the Circular of the Supreme Court of the Republic of Indonesia concerning interfaith marriage is to protect Human Rights in line with the principles of maqāṣid al-sharī‘ah such as protection of religion and descent, but on the other hand, it creates conflict with the principles of Human Rights which are also part of the principles of maqāṣid al-sharī‘ah. The researcher argues that the principle of maqāṣid al-sharī'ah should be able to balance religious values and Human Rights in interfaith marriages, by being used as the legal basis and policies related to interfaith marriages. This research can be used as a consideration for policy reform to realize balance and justice for the parties in line with the principle of maqāṣid al-sharī‘ah.